Formation of Gold Particles via Thiol Groups on Glycoconjugates Comprising the Sheath Skeleton of Leptothrix. Issue 3 (16th March 2019) - Kunoh, Tatsuki; Kusano, Yoshihiro; Takeda, Minoru; Nakanishi, Makoto; Matsumoto, Syuji; Suzuki, Ichiro; Takano, Mikio; Kunoh, Hitoshi; Takada, Jun
Abstract: Leptothrix, iron-oxidizing bacterium, produces microtubular sheaths that surround the catenulate cells. Organic nanofibrils excreted from the cell surfaces interweave and coalesce to form immature sheaths, which attract aqueous-phase inorganics to eventually form mature organic–inorganic sheaths. Such inorganic encrustation of the sheaths results from interactions between functional groups in the sheath skeleton and inorganics. Based on our previous findings that Leptothrix sheath skeleton sorbed 47 inorganics (Au was one of the most abundant adsorbates), we examined the sorption status of Au cations on cell-enclosing sheaths and their protein-free remnants and found that nano to sub-micron Au particles (AuNPs and AuSMPs, respectively) formed on the sheath-forming polymer consisting of a glycoconjugate (an amphoteric glycan modified with cysteine, glycine, and 3-hydroxypropionic acid). When the purified polymer was incubated in HAuCl4 solution, AuNPs and AuSMPs formed on the polymer surfaces. Both particles formed also on cell-enclosing sheaths and protein-free sheath remnants incubated in HAuCl4 solution. When SH groups in the cell-enclosing sheaths were masked with a fluorescent protein, Au particles did not form after incubation in HAuCl4 solution. Results implicate that SH groups are at least partially involved in the reduction of Au cations to metallic Au and eventual formation of Au particles.